The Plant Production in Norway - Dorota Kozioł-Kaczorek (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
A problem of the Norwegian agricultural policy, a description of the current types of subsidies for plant production and ongoing changes in the plant production in the years 2001 – 2016 is presented in this paper. There are also short information about topography of Norway and climate conditions. The main aim of the publication is to characterize changes in the plant production in the considered period. There is not too many publications about the Norwegian agriculture and plant production. The data from Statistiska Sentralbyrå (Statistics Norway) were used in the quantitative analysis. The results indicate the slight changes in the plant production in Norwegian agriculture i.e. decrease of number of holdings with plant, decrease of area of crops and size of yields.